2015
DOI: 10.3201/eid2103.140927
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniaeandChlamydiaspp. Infection in Community-Acquired Pneumonia, Germany, 2011–2012

Abstract: M. pneumoniae infections showed a strong epidemic peak, but Chlamydia spp. were consistently detected throughout the year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 39 publications
8
87
3
Order By: Relevance
“…The proportions of MLVA and P1 types were reported to vary among geographic regions, as has the prevalence of macrolide resistance-associated mutations (9)(10)(11)20,21). We also reported P1 types and the prevalence of macrolide resistance-associated mutations of M. pneumoniae isolates in Yamagata, Japan between 2004 and 2013 (22).…”
Section: Introductionmentioning
confidence: 63%
“…The proportions of MLVA and P1 types were reported to vary among geographic regions, as has the prevalence of macrolide resistance-associated mutations (9)(10)(11)20,21). We also reported P1 types and the prevalence of macrolide resistance-associated mutations of M. pneumoniae isolates in Yamagata, Japan between 2004 and 2013 (22).…”
Section: Introductionmentioning
confidence: 63%
“…Therefore, an implication of Simkania in respiratory diseases, especially in children and young adults, cannot be ruled out and requires further investigations. Despite the questionable reliability of some of the older studies that did not include controls, cases of Simkania infection were identified even in recent studies, either as the only putative pathogen or with other organisms (Dumke et al, 2015;Fasoli et al, 2008;Heiskanen-Kosma et al, 2008;Nascimento-Carvalho et al, 2009). The identification of a few patients with either a specific Simkania-associated pneumonia or bronchiolitis suggests that it might be effectively a true pathogen and might be problematic in endemic regions.…”
Section: Future Challenges and Conclusionmentioning
confidence: 99%
“…These findings are similar to what is observed for C. pneumoniae, whose pathogenic role is nevertheless commonly accepted. Recent studies reported a prevalence of C. pneumoniae infection of <2% in patients suffering from community acquired pneumonia (Dumke et al, 2015;Pletz et al, 2011;Senn et al, 2011;Wellinghausen et al, 2006). In addition, the correlation between serology and direct identification of C. pneumoniae through PCR is not good (Wellinghausen et al, 2006) and might be explained by a delay (2-3 weeks) in the apparition of IgM (Kuo et al, 1995).…”
Section: Future Challenges and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell wall-less bacterium causes infections of the respiratory tract, including severe interstitial pneumonia (1), and usually accounts for 5 to 10% of all cases of community-acquired pneumonia among pediatric (2) and adult (3) patients. Because of the timedependent incidence of infections, Ͼ25% of pneumonia cases in epidemic periods are attributed to this agent (4). In addition, a number of extrapulmonary manifestations and complications are described, affecting mainly the skin and the central nervous system (5).…”
mentioning
confidence: 99%